2008
DOI: 10.3998/ark.5550190.0009.227
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acid catalyzed N-acylation of carbamates and oxazolidinones

Abstract: The reaction of various carbamates and oxazolidinones with carboxylic acid anhydrides in presence of Lewis acid catalysis is described. The N-acylation was effectively promoted by catalytic amount of ZnCl 2 to produce the corresponding N-acyl products in good yields under solvent-free conditions. Carboxylic acids were also successfully used as acylating agents via mixed anhydride method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In order to conduct condensation reactions of these non-nucleophilic nitrogen compounds with carboxylic acids, prior formation of an anionic species by deprotonation of the N–H by a stoichiometric strong metal base such as n -butyllithium or NaH and/or the use of an activated carboxylic acid derivative such as an acid halide or activated ester is usually required. For example, Snider reported N -acylation of a tryptophan derivative by using a p -nitrophenyl ester as an acylation reagent .…”
mentioning
confidence: 99%
“…In order to conduct condensation reactions of these non-nucleophilic nitrogen compounds with carboxylic acids, prior formation of an anionic species by deprotonation of the N–H by a stoichiometric strong metal base such as n -butyllithium or NaH and/or the use of an activated carboxylic acid derivative such as an acid halide or activated ester is usually required. For example, Snider reported N -acylation of a tryptophan derivative by using a p -nitrophenyl ester as an acylation reagent .…”
mentioning
confidence: 99%
“…To support this reasoning, a search for a more effective acylation catalyst was carried out. A retrieval of literature revealed that FeCl 3 , and FeCl 3 ·6H 2 O can catalyze acylation of alcohols, amines, and carbamates using carboxylic anhydrides as acylating agents. We wondered whether FeCl 3 and other Lewis acids listed in Table , which are reactive for deacylation of N -acylsulfonamides, could be tailored to mediate the acylation of sulfonamides.…”
Section: Resultsmentioning
confidence: 99%
“…To support this reasoning, a search for a more effective acylation catalyst was carried out. A retrieval of literature revealed that FeCl 3 54,55 and FeCl The scope of this acylation reaction was probed using FeCl 3 as the catalyst (Scheme 4). As expected, a number of primary and secondary sulfonamides bearing various functional groups were efficiently acetylated using Ac 2 O as the acylation agent.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We attempted ZnCl 2 mediated direct N -trifluoroacetylation based upon the ZnCl 2 mediated N -acylation of carbamates and oxazolidinones reported by Reddy and co-workers. 35 Accordingly, boc-derivative 10 was treated with 10% ZnCl 2 and 2 equivalents of trifluoroacetic anhydride in CH 2 Cl 2 at 23 °C for 12 h to provide the N -trifluoroacetamide derivative 8a in 91% yield as a single diastereomer.…”
Section: Resultsmentioning
confidence: 99%
“…Reddy and co-workers utilized ZnCl 2 -mediated acylation of Cbz-protected derivatives; however, their efforts to carry out N -acylation of boc-protected derivatives were unsuccessful. 35 The N -trifluoroacetyl protected amine 8a was then converted to target acid 2 by lithium hydroxide saponification in 83% yield. Carboxylic acid 2 was crystallized directly from the crude mixture in a solution of 1 : 4 THF/hexanes.…”
Section: Resultsmentioning
confidence: 99%